Rodzima Wiara (nie) tylko dla mężczyzn. O upłciowieniu prawicowego neopogaństwa słowiańskiego w Polsce - Filip, Mariusz (My University, 2014)
At the time of its existence Zakon Zadrugi “Północny Wilk” was a male society. In the ideology of this group, Paganism and masculinity are strongly inter-connected. The rule “for men only” is also strongly exercised in everyday and ritual life. Taking these observations as a starting point for further considerations, I explore the position(s) of women in this male world. First, I focus on the male perspective, presenting two rival views of the male-female relationship: subordination and partnership. Second, I demonstrate how women negotiate their position within the Wolves. I will discuss one way of responding to these conditions in particular: the formation of Bogini Wojny based on the opposite principle, “for women only.”
Native Faith (not) only for men: About gendering right-wing Neopaganism in Poland